2017
DOI: 10.3389/fpsyg.2017.01633
|View full text |Cite
|
Sign up to set email alerts
|

“Health in the Mirror”: An Unconventional Approach to Unmet Psychological Needs in Oncology

Abstract: Background: The introduction of aesthetic care programs for cancer patients inside hospitals could help patients cope with the side effects of both disease and treatment. The specific objective of this study is to evaluate whether a complementary and supportive program, called “Health in the Mirror,” has a positive effect on participants by analyzing certain psychological variables. Methods: Eighty-eight female cancer patients were included in this analysis. The support progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…Research on the immediate and short‐term effects of beauty care interventions in breast cancer patients, however, is less clear: It was consistently found that perception of attractiveness was improved, and symptoms of depression and anxiety were immediately decreased by beauty care . While these results support the idea that beauty care has beneficial effects on psychological outcomes on the short term, no conclusions can yet be drawn about their specificity, reliability, and stability because of a lack of control groups (including randomized assignment), low‐sample sizes, and short or absent follow‐ups.…”
Section: Introductionmentioning
confidence: 98%
“…Research on the immediate and short‐term effects of beauty care interventions in breast cancer patients, however, is less clear: It was consistently found that perception of attractiveness was improved, and symptoms of depression and anxiety were immediately decreased by beauty care . While these results support the idea that beauty care has beneficial effects on psychological outcomes on the short term, no conclusions can yet be drawn about their specificity, reliability, and stability because of a lack of control groups (including randomized assignment), low‐sample sizes, and short or absent follow‐ups.…”
Section: Introductionmentioning
confidence: 98%
“…Noticeably, a quantitative assessment showed that participating in the Health in the Mirror program fostered a significant reduction in depressive symptoms, anxiety and body image issues, both immediately at the conclusion of the program and 3 months later. Remarkably, self-esteem levels showed an improvement at the 3-months follow-up (Di Mattei et al, 2017).…”
Section: Health In the Mirrormentioning
confidence: 83%
“…For instance, chemotherapy is often associated with cosmetic side effects, including alopecia, paleness, dry skin, and weight loss or gain (Amiel et al, 2009). These adverse reactions can represent for patients a source of distress comparable to the disease itself (Di Mattei et al, 2016Mattei et al, , 2017. Notably, the aesthetic consequences of therapies, such as hair loss, can be experienced in terms of a real trauma, especially by the female population (Lemieux et al, 2008), leading to anxiety and depression symptoms (Stafford et al, 2015).…”
Section: Self-esteem and Cancermentioning
confidence: 99%
See 2 more Smart Citations